Game of Snipers - Hunter, Stephen, 1946-; Bray, R. C (Grand Haven, Michigan : Brilliance Audio, 2019)
Obsessively tracking a sniper with skills that match his own, Bob Lee Swagger teams up with the Mossad, the FBI, and local law enforcement to identify the killers next target.
Keywords: Swagger, Bob Lee (Fictitious character) -- Fiction; Snipers -- Fiction; Suspense fiction